Right to respect for family life: problems of the application of the European Court of Human Rights’ practice concerning forced return to Ukraine and banishment from Ukraine - Yaremko, Oksana (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The problem of the non-use by Ukrainian courts of the judicial practice of the European Court of Human Rights concerning the right to respect for family life upon consideration of the cases on the forced return to Ukraine and banishment from Ukraine of the foreigners or stateless persons have been researched in the article. It is pointed out on the insufficiency of consideration upon consideration of the cases on the forced return to Ukraine and banishment from Ukraine of only the fact of violation of legislation on migration by the foreigner or stateless person as well as of the fact of avoiding of exit out of the country at the expiration of the allowed period of residence. It is noticed that such judgements should be entered proportionally in particular with keeping necessary balance between unfavourable consequences for the rights, freedoms and interests of the person and the aims, on achievement of which those decisions are directed